Thermal Stress Indices in Young Nellore Bulls Raised in Tropical Environments - Storti, Andressa Alves; de Mattos Nascimento, Maria Regina Bueno; de Faria, Carina Ubirajara; Marques da Silva, Natascha Almeida (Acta Scientiae Veterinariae, 2019)
Background: Thermal stress indices are important in predicting and choosing means for mitigating heat stress and defining critical environmental conditions for animal welfare and performance. The aim of this study was to determine the association between 16 thermal stress indices and thermophysiological variables in young Nellore bulls raised in a tropical pasture to determine the most effective parameter of heat stress to assist in the management of the thermal environment and animal welfare. Materials, Methods & Results: Seventy-eight young Nellore bulls (Bos taurus indicus), with a mean age of 10.5 months and mean body weight of 242.09 ± 32.17 kg at first collection, and 17.92 months and body weight 335.80 ± 39.02 kg at last collection, were used. During the experimental period, rectal temperature (RT) and surface temperature at the forehead, scapula, and groin, from which the average surface temperature (AST) was calculated, were measured. The difference between the AST and air temperature (i.e., AST – AT) and between the RT and AST (i.e., RT – AST) defined the thermal gradient. For the evaluation of thermal environment, the dry bulb, wet bulb, and globe temperatures, and wind speed were measured. Relative humidity, mean radiant temperature, solar radiation, temperature humidity index (THI), black global temperature humidity index (BGHI), equivalent temperature index (ETI), environmental stress index (ESI), respiratory rate predictor (PRR), heat load index (HLI), comprehensive climate index (CCI), and index of thermal stress for cows (ITSC) were calculated. The average and maximum air temperatures were above thermal comfort levels, while the average relative humidity was within the ideal limit for cattle. The average globe temperature was higher than the air temperature. Solar radiation presented very high values and wind speeds were very low. RT indicated normothermia in the cattle, and AST and thermal gradient (i.e., AST – AT) indicated thermal comfort. The 16 thermal stress indices demonstrated a significant positive and moderate correlation with AST, but were not significantly correlated with RT. Discussion: The average (28.14°C) and maximum (31.90°C) air temperatures indicated discomfort, since the ideal temperature for cattle is ≤ 27°C. The high thermal load of this region can contribute to poor animal welfare, thus requiring the provision of natural or artificial shade for pasture farming. The cattle in this study were in thermal equilibrium given that they maintained RT within the normal range, and the maximum limit was higher. If RT is maintained within physiological limits, the mechanisms of thermoregulation are able to eliminate excess heat (i.e., thermolysis is equivalent to thermogenesis). The AST was 5.4°C below the RT. It is important to note that deep body temperature (i.e., RT) is more stable than the surface body temperature, which is influenced by ambient temperature. Considering that there was no correlation between thermal stress indices and RT, and that the cattle were able to maintain RT within physiological limits, the Nellore bulls in this study were adapted to the environment. The thermal stress indices evaluated in this study adequately reflected heat stress in young Nellore bulls raised in pastures in a tropical environment. Surface temperature was the physiological parameter that responded most significantly to environmental conditions.